THE NIGER DELTA PHENOMENON FROM THE PERSPECTIVES OF SARTRE’S EXISTENTIALISM AND SOCIAL POSITIVISM - Ncha Gabriel Bubu (Universitas PGRI Madiun, 2021)
To some, existentialism and positivism in bipolar thinking, are dichotomies, others view them as related concepts in philosophy. It is a considered view of this paper that these two schools of thought are related, complementary and have a relationship that is useful in conflict resolution. This assertion is examined in this analysis vis-à-vis the Niger Delta, is the trust of this paper.